STRENGTHENING THE AFFECTIVE SPACE IN THE IMPLEMENTATION OF PANCASILA STUDENT PROFILES AT THE MUHAMMADIYAH KEPONG MALAYSIA GUIDANCE SCHOOL - Padang, Aisyah R.D.N.; Sari, Suci Perwita; Nst, Ismail Saleh; Nasution, Dewi Kesuma (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The purpose of this study was to determine the Strengthening of the Affective Domain in the Implementation of Pancasila Student Profiles in the Kepong Muhammadiyah Muhammadiyah Guidance Center, Malaysia. This research is a qualitative field research. The method or approach used is descriptive research, which means the researcher tries to find the elements, characteristics, characteristics of a phenomenon. This research was carried out by the Muhammadiyah Kepong Malaysia Guidance Center. Determination of informants in this study using a purposive sampling technique, namely how to determine informants who have been determined deliberately according to predetermined criteria. Researchers will record, record, and observe the behavior of these informants. The informants in this study were school principals, educators, and students of the Muhammadiyah Kepong Malaysia Guidance Studio. The types and sources of data are in the form of Primary data and Secondary data. Primary data was obtained directly through interviews with sources from research informants, namely school principals, education staff and students of Muhammadiyah Kepong Malaysia Learning Studio. Secondary data is research supporting data such as documents, activity results reports, through words and actions from research informants and research subjects related to the implementation of the Merdeka Learning Program Through Pancasila Student Profiles at the Kepong Muhammadiyah Muhammadiyah Guidance Center, Malaysia. Data collection techniques in this study are through observation, interviews, and documentation. The interview technique in this study used a structured interview technique, in which the interviewer determined the problems and questions to be asked, in other words, the researcher already knew the information would be obtained and had written down the questions in the interview guide. The results of this study indicate that the implementation of the Pancasila Student Profile in the Muhammadiyah Kepong Malaysia Guidance Studio is implemented through the Pancasila Student Profile Strengthening Project (P5) using a project-based approach. Students are invited to identify problems that exist around them and create projects to solve them. The Implementation of the Project to Strengthen Pancasila Student Profiles Muhammadiyah Kepong Malaysia Guidance Workshop consists of 3 themes, namely: Local wisdom, sustainable living, and entrepreneurship. Factors supporting the implementation of the Pancasila Student Profile in the Kepong Muhammadiyah Muhammadiyah Guidance Center, Malaysia, namely: 1). Collaboration of all school parties, 2). Student participation. The inhibiting factors for the implementation of the Pancasila Student Profile in the Muhammadiyah Kepong Malaysia Guidance Center are: 1). Different characteristics of students, 2) Number of student ratios, 3). Lack of accompanying teachers, 4). New curriculum.